2006
DOI: 10.1093/carcin/bgl236
|View full text |Cite
|
Sign up to set email alerts
|

PSA/KLK3 AREI promoter polymorphism alters androgen receptor binding and is associated with prostate cancer susceptibility

Abstract: The proximal promoter of the kallikrein-related peptidase 3 gene (KLK3/PSA) contains a single-nucleotide polymorphism (G-158A) located within the second canonical half-site for the prostate-specific antigen (PSA) androgen response element 1 (AREI). Previous studies suggest that this polymorphism may be associated with higher PSA levels and increase prostate cancer risk. We have investigated the potential functional significance of this polymorphism and its association with prostate cancer susceptibility by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 25 publications
4
46
1
1
Order By: Relevance
“…Moreover, there are several other KLKs that are upregulated in ovarian cancer versus normal tissue, but which are markers of improved prognosis, namely KLK8, KLK9 and KLK14 (Borgono et al, 2004;Obiezu & Diamandis, 2005). Although it is perhaps surprising that rs266882 was not found to be associated with ovarian cancer survival despite the reported functional significance of this SNP, this may also reflect some fundamental differences in regulation of PSA expression between prostate and ovarian cancer, namely differential tissue-specific co-regulator binding at the allelic change in the AREI as suggested for rs266882 in prostate cell lines (Lai et al, 2007), which may drive differential ovarian expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are several other KLKs that are upregulated in ovarian cancer versus normal tissue, but which are markers of improved prognosis, namely KLK8, KLK9 and KLK14 (Borgono et al, 2004;Obiezu & Diamandis, 2005). Although it is perhaps surprising that rs266882 was not found to be associated with ovarian cancer survival despite the reported functional significance of this SNP, this may also reflect some fundamental differences in regulation of PSA expression between prostate and ovarian cancer, namely differential tissue-specific co-regulator binding at the allelic change in the AREI as suggested for rs266882 in prostate cell lines (Lai et al, 2007), which may drive differential ovarian expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous subsequent studies have revealed conflicting results. Some have reported an association with the same allele as the original study (Gsur et al , 2002 ;Medeiros et al , 2002 ;Cicek et al , 2005 ;Lai et al , 2007 ), while others have reported either a significant association in the opposite direction (Chiang et al , 2004 ;Binnie et al , 2005 ) or no association for this SNP (Wang et al , 2003 ;Salinas et al , 2005 ;Mononen et al , 2006 ;Severi et al , 2006 ;Cunningham et al , 2007 ;Pal et al , 2007 ;Penney et al , 2011 ). A meta-analysis of all studies published up until 2008 reported no evidence of association with prostate cancer risk overall (Supplementary Table 1; Jesser et al , 2008 ).…”
Section: Pre-gwas Klk Candidate Gene-association Studiesmentioning
confidence: 96%
“…Functional studies on rs266882 attribute KLK3 gene expression alteration to differential binding of ARE1 to the androgen receptor (Table 1) and enhanced transcriptional response to androgens. They also show increased prostate cancer susceptibility in the presence of A/A genotype (three-fold risk) and A/G genotype (2.4-fold risk; Lai et al , 2007 ).…”
Section: Functional Klk Snps: Experimental Validationmentioning
confidence: 99%
“…Several single nucleotide polymorphisms in this gene and their possible association with the risk of prostate cancer and serum PSA levels have been studied. Until recently, the single nucleotide polymorphism (SNP) at -158 G/A has been the most studied polymorphism of the PSA gene, but no consensus about its significance in prostate cancer has been reached thus far (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Cramer et al reported a possible association between SNPs in the enhancer region of the PSA gene and serum PSA levels (22).…”
Section: Introductionmentioning
confidence: 99%